Supply-side Strategy Implications on Demand-side Opportunities - Austin, Stephen B. (Distributed Generation & Alternative Energy Journal, 2008)
Major changes in the gas and electric markets have created a range of risk management products to support supply-side planning. The supply-side goal is usually to balance a client’s tolerance for cost fluctuations with the lowest possible price. There are many implications a supply strategy has on demand-side opportunities. They should be considered carefully. This integration of supply and demand-side plan- ning often does not take place because they have been thought of as two independent disciplines. They require two separate sets of expertise. Historically, demand-side planning has been a responsibility for engineering and operations while supply-side planning was the domain of purchasing and procurement. The integration of supply and demand is critical to control of your total energy picture. The right hand needs to know what the left hand is doing. There are a number of situations that illustrate where an integrated supply and demand-side approach is vitally important. This article will examine two situations as examples. We will show how your supply-side strategy affects your true energy costs and how that is different than in the past. We will also show how a supply-side strategy gives new triggers for demand-side actions.